2016
DOI: 10.1007/s00223-016-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

GDF11 Inhibits Bone Formation by Activating Smad2/3 in Bone Marrow Mesenchymal Stem Cells

Abstract: Growth differentiation factor 11 (GDF11) is a member of the transforming growth factor-β superfamily. Recent studies confirmed that GDF11 plays an important role in regulating the regeneration of brain, skeletal muscle, and heart during aging; however, its role in bone metabolism remains unclear. Thus, the aim of this study was to determine the effects of GDF11 on bone metabolism, including bone formation and bone resorption, both in vitro and in vivo. Our results showed that GDF11 inhibited osteoblastic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…In contrast, growth differentiation factor GDF11/BMP11 has been identified as a rejuvenating factor for neuronal tissue, vasculature, cardiac and skeletal muscle; however, due to the high similarity of GDF11 to myostatin/GDF8, there are doubts about the specificity of these data [21]. Adding to this controversy and enforcing the earlier notion that a general increase in TGF-β/BMP signaling is detrimental, GDF11 has been shown to accelerate age-related bone loss in mice [22]. …”
Section: Mammalian Epimorphic Regeneration: Major Steps and The Impacmentioning
confidence: 77%
“…In contrast, growth differentiation factor GDF11/BMP11 has been identified as a rejuvenating factor for neuronal tissue, vasculature, cardiac and skeletal muscle; however, due to the high similarity of GDF11 to myostatin/GDF8, there are doubts about the specificity of these data [21]. Adding to this controversy and enforcing the earlier notion that a general increase in TGF-β/BMP signaling is detrimental, GDF11 has been shown to accelerate age-related bone loss in mice [22]. …”
Section: Mammalian Epimorphic Regeneration: Major Steps and The Impacmentioning
confidence: 77%
“…This concept, however, has been challenged by the findings of several different labs [8890]. Most recently, it was shown that overexpression of GDF11 in mice induces muscle atrophy, inhibits skeletal muscle regeneration, leads to bone loss, and blocks bone resorption; all outcomes that argue that increasing GDF11 would not be a beneficial strategy for musculoskeletal health [73, 89, 91, 92]. We found that the average expression of Gdf11 decreases approximately 17% in iMS Bmal1 −/− mice 5 weeks post knockout of Bmal1 .…”
Section: The Effect Of Bmal1 Knockout In Muscle On Bonementioning
confidence: 99%
“…bone formation and induces bone loss in mice. 18 The results of in vivo studies, which may more accurately reflect actual conditions, have demonstrated that GDF11 inhibits bone formation. [18][19][20] The GDF11 amino acid sequence is 90% identical to that of myostatin (GDF8).…”
Section: Recent Data Show That Intraperitoneal Injection Of Gdf11 Inhmentioning
confidence: 99%
“…18 The results of in vivo studies, which may more accurately reflect actual conditions, have demonstrated that GDF11 inhibits bone formation. [18][19][20] The GDF11 amino acid sequence is 90% identical to that of myostatin (GDF8). [21][22][23] Previous studies have documented that mice with myostatin deficiency present increased osteogenic differentiation and bone mass compared to wild-type mice.…”
Section: Recent Data Show That Intraperitoneal Injection Of Gdf11 Inhmentioning
confidence: 99%